CURATIVE CARE THROUGH ADMINISTRATION OF PLANT-DERIVED MEDICINES IN SEKHUKHUNE DISTRICT MUNICIPALITY OF LIMPOPO PROVINCE, SOUTH AFRICA - Rankoana, Agnes Sejabaledi (African Journal of Traditional, Complementary and Alternative Medicines, 2016)
Background: Ajuga bracteosa and Viola odorata are frequently used by the native people of Swat-Pakistan for the curing of fever, malaria, cough, urinary and stomach disorders with slightly different practice of usage like raw powdered, extracts, decoction etc. Methods and Materials: Disc Diffusion Method was used for determination of antimicrobial activities of both plants. Nutrient Agar Media was used for the culturing and growth of all microbial strains. Vitamin C and minerals contents were determined by standard method of AOAC. Na and K were analyzed by using flame photometric technique. Micro minerals i.e. “Ni, Cr, Fe, Cu, Zn, Mn, Ca, Pb, and Mg” were determined by Atomic Absorption Spectrophotometer (AAS). Total Soluble Solid (TSS) was determined by using abbe refractometer and pH was determined by using pH meter. Results: The present study demonstrates that both plants exhibited antibacterial activities against P. aeruginos, E. coli, S. typhi, B. subtilis and S. aureus. The examined plants showed zone of inhibition for aqueous fraction (50.90, 45.90 %) against P. aeruginosa; for EtOAc fraction (41.37, 57.62%) against C. Albicans and for hexane fraction (25.86, 40.57%) against K. pneumoniae, respectively. Total of 14 different minerals (Na, K, P, Ca, Mg, Fe, Zn, Mn, Co, Cr, Ni, Cu, Pb, Cd) were determined and it was also observed that both the examined plants contained significant level of these analyzed minerals. The subject plants contained highest level of magnesium (295.75, 145.85 mg 100-1g) and calcium (212.49, 44.00 mg 100-1g) and potassium (152.6, 437.45 mg 100-1g) while moderate level P, Zn, Na and lower amount of Cd, Ni, Mn and Cu using Atomic Absorption, Flame Photometry and spectrophotometric techniques. V. odorata was found to contain a higher amount of vitamin C (64.05±12.37mg 100-1g) as compared to A. bracteosa (45.45 ± 7.29 mg 100-1 g). Conclusion: Findings of this study can persuade researchers for future comprehensive phytochemical study of these plants using state of art techniques and instruments, which include not only isolation of secondary metabolites from these plants but biological evaluation of isolated compounds both in vivo and in vitro